Rehabilitation Medicine in Pellegrini-Stieda Syndrome with Myositis Ossificans and Neglected Patella Fracture - Ronni Untung Handayanto; Tanti Ajoe Kesoema; Rahmi Isma AP (Indonesian Journal of Physical Medicine & Rehabilitation, 2018)
Introduction: Pellegrini-Stieda Syndrome (PSS) is calcification of the medial collateral ligament(MCL). The manifestation are restricted motion and pain of the knee. PSS usually associated withtrauma or repeated strain.Methods: A case report of 30 year old physically active men has a severe stiffness and pain on the leftknee while walking for six months. He had neglected trauma 9 years ago. There were antalgic gait,mild swelling, warm, and tenderness on medial aspect, restricted range of motion (ROM) by pain on theleft knee; flexion 150. The knee X-Ray has shown the myositis ossificans and Pellegrini-Stieda lesion.Subject had undergone Rehabilitation Program, i.e. progressive gradual motion exercise and cryotherapyResults: There were reduced of pain, and increase the Left knee PROM were 15º restricted of extensionand 30º flexion, became 8ºrestricted of extension and 55º flexion, after one month of program.Conclusion: Pellegrini-Stieda Syndrome (PSS) is a possible complication in major knee trauma. Thepatient showed improvements in pain, and ROM after one month of rehabilitation programs.Keywords: Pellegrini-Stieda Syndrome (PSS), Range-of-Motion (ROM), Medial Collateral Ligament(MCL).